Speed Distributional Trends on Two-lane Roads with Mixed Traffic under Heavy Flow. (2017) - Roy, Rupali; Saha, Pritam; Sarkar, Ashoke Kumar
Abstract: The present paper describes a method of modelling speed data on two-lane roads under heavy flow when traffic is heterogeneous in character. The effect of heterogeneity in traffic mix results in deviation of speed distribution model from normal distribution. This effect further exaggerates particularly at heavy flow because of frequent interaction of vehicles in the traffic stream. Thus, there is a need to develop a method of modelling speeds on these roads at such flow condition. On the basis of field data collected on a major intercity road in India, the present study made it evident that skewness of speed data is significantly high under heavy flow situation. This attributes to the fact that majority of vehicles in the traffic stream are entrapped inside platoons and their speed is influenced greatly. The present study, accordingly, examined the distribution of these data and concluded that their logarithmic transformation reasonably satisfies the normality assumption while modelling in terms of goodness-of-fit.